2008
DOI: 10.2174/138161208783330772
|View full text |Cite
|
Sign up to set email alerts
|

Drug Loaded Erythrocytes: As Novel Drug Delivery System

Abstract: Novel drug delivery systems are one of the widely used delivery systems. In the present scenario, amongst them, "Drug Loaded Erythrocytes" is one of the growing and potential systems for delivery of drugs and enzymes. Erythrocytes are biocompatible, biodegradable, possess long circulation half-life and can be loaded with variety of biologically active substances. Carrier erythrocytes are prepared by collecting blood sample from the organism of interest and separating erythrocytes from plasma. By using various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…5B-5D also confirms only minor morphological perturbations to the SSRBCs following hypotonic pre-swelling loading of calcein. The calcein entrapment efficiency, determined by flow cytometry measurements of the fraction of cells detected with measureable fluorescence compared to all counted cells, was about 85% which is consistent with reported loading efficiencies for this method in nRBCs [25-26]. …”
Section: Resultssupporting
confidence: 87%
“…5B-5D also confirms only minor morphological perturbations to the SSRBCs following hypotonic pre-swelling loading of calcein. The calcein entrapment efficiency, determined by flow cytometry measurements of the fraction of cells detected with measureable fluorescence compared to all counted cells, was about 85% which is consistent with reported loading efficiencies for this method in nRBCs [25-26]. …”
Section: Resultssupporting
confidence: 87%
“…This resealing procedure has been widely used by other researchers over the years with MERs. 23,24 At the end of this process, the NERs are expected to have intact, sealed membranes. At this point, while the NERs are loaded with solute, free solute is also present in the external solution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For example, red blood cell membranes have been used to coat NPs as well as to generate nanovesicles with liposome-like features in terms of drug loading and release capabilities [154,158]. Hu et al demonstrated that red blood cell molecules were correctly transferred and oriented on the NPs surfaces [159].…”
Section: Evading the Immune Systemmentioning
confidence: 99%